As Tecnologias da Informação e Comunicação e a construção do conhecimento pelo aluno surdo. - Klimsa, Severina Batista de Farias (2006)
This objective research to analyze the use of the Technologies of the Information and Communication TIC s - as mediating resources and/or facilitate in the education of deaf pupil e, concomitantly, in the construction of the discovery process, leaving of the practical apprehension of the daily one of a special room. In more specific level, it is intended: to point out the TIC s in the ballast of the control society, being verified as the technological speech directs it practical the educative pertaining to school; to argue the education of deaf people, pointing the methodologies used in the construction of the knowledge in special/inclusive rooms; to mediate practical daily of the pupils in the lessons being used the technology as methodology tool, to propitiate the construction of the knowledge and the access to the information. One works with the hypothesis that the TIC s is used of different resources multimedia - mediating/facilitate - that they propitiate the education of deaf pupil e, consequently, the construction of the knowledge. Although the resources facilitate to the process and the production of the knowledge of the pupil, salient that they discipline and control the behavior of the pupils - deaf or not -, when using itself of deriving tactics of the control society.